027 Eosinophilia and lymphocytosis after natalizumab for relapsing-remitting multiple sclerosis. Issue 6 (27th May 2022) - Keshvari, Milad-Kazava; Sheikh, Saima; Someren, Fred van; Galea, Ian
Abstract : Background: Natalizumab (NTZ), a humanized monoclonal antibody against the integrin VLA4, is a highly effective treatment for relapsing-remitting multiple sclerosis. Eosinophilia and lymphocytosis may occur, but their frequency, kinetics, risk factors, consequences and ideal monitoring frequency are unknown. Methods: Here we present preliminary results from an ongoing retrospective review of the medical and haematological electronic records of 195 patients in a multiple sclerosis specialist centre, who had started NTZ between January 2008 and April 2019, received NTZ up to January 2020, had at least two doses and had blood results available. Results: The study included 833 patient-years of NTZ exposure. 72% were female. Mean age was 37.1 years (standard deviation: 10.2 years). Only 3.6% of NTZ doses were missed. 6% were JC virus seroposi- tive before NTZ was started. Of the JC-seronegative patients before NTZ was started, 32% seroconverted whilst on NTZ. The mean eosinophil and lymphocyte count whilst on NTZ was above the reference range in 14% and 25% of patients. The kinetics, risk factors, and consequences of these two haematological abnormalities will be presented in detail. Conclusion: Eosinophilia and lymphocytosis are common, and have clinical and service implications, affecting medical management and monitoring frequency. Data presented will inform practice. milad_kazava@yahoo.co.uk